Nephroprotective Effect of Mesenchymal Stem Cell-Based Therapy of Kidney Disease Induced by Toxicants - Shujun Lin; Wenshan Lin; Chunling Liao; Tianbiao Zhou (Stem Cells International)
Background. Renal damage caused by drug toxicity is becoming increasingly common in the clinic. Preventing and treating kidney damage caused by drug toxicity are essential to maintain patient health and reduce the social and economic burden. In this study, we performed a meta-analysis to assess the nephroprotective effect of mesenchymal stem cells (MSCs) in the treatment of kidney disease induced by toxicants. Methods. The Cochrane Library, Embase, ISI Web of Science, and PubMed databases were searched up to December 31, 2019, to identify studies and extract data to assess the efficacy of MSCs treatment of kidney disease induced by toxicants using Cochrane Review Manager Version 5.3. A total of 27 studies were eligible and selected for this meta-analysis. Results. The results showed that a difference in serum creatinine levels between the MSC treatment group and control group was observed for 2, 4, 5, 6-8, 10-15, 28-30, and ≥42 days (2 days: WMD=−0.88, 95% CI: -1.34, -0.42, P=0.0002; 4 days: WMD=−0.74, 95% CI: -0.95, -0.54, P<0.00001; 5 days: WMD=−0.46, 95% CI: -0.67, -0.25, P<0.0001; 6-8 days: WMD=−0.55, 95% CI: -0.84, -0.26, P=0.0002; 10-15 days: WMD=−0.37, 95% CI: -0.53, -0.20, P<0.0001; 28-30 days: WMD=−0.53, 95% CI: -1.04, -0.02, P=0.04; ≥42 days: WMD=−0.22, 95% CI: -0.39, -0.06, P=0.007). Furthermore, a difference in blood urea nitrogen levels between the MSC treatment group and control group was observed for 2-3, 4-5, 6-8, and ≥28 days. The results also indicate that MSC treatment alleviated inflammatory cells, necrotic tubules, regenerative tubules, and renal interstitial fibrosis in kidney disease induced by toxicants. Conclusion. MSCs may be a promising therapeutic agent for kidney disease induced by toxicants.